9.6=2.4z

Simple and best practice solution for 9.6=2.4z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9.6=2.4z equation:



9.6=2.4z
We move all terms to the left:
9.6-(2.4z)=0
We add all the numbers together, and all the variables
-(+2.4z)+9.6=0
We get rid of parentheses
-2.4z+9.6=0
We move all terms containing z to the left, all other terms to the right
-2.4z=-9.6
z=-9.6/-2.4
z=+4

See similar equations:

| 2(1.5m+3)=3.5m–1 | | 5a–3=3a+23 | | x+8.2=12.2 | | x+4=16; | | 8q-4=q+3 | | 0.45=16.95−0.25(76−5x) | | x10+1=13 | | 10+8v=10+3v | | 16x2-4x+1=0 | | s+52/–8=–3 | | 3w-4=6-2w | | 48+1.5h=36 | | 1.6x=10.4 | | 7+6r=10r-5 | | 2.6Xx=10.4 | | 3−10x-16=9−10x+14 | | `3x+7=13` | | 1=n/4−2 | | −10x-16=9−10x+14 | | 6c-3=9-3+5c | | (5x-4)/6=-4 | | 2f+-8=-18.34 | | n+27=61 | | n/3+15=23 | | n3+ 15=23 | | 7x–4(x+4)+20=25 | | 3c+2c=90 | | Sx6=34 | | 2+3y=-25 | | 7(3x-1)+62=6(2x+7) | | 6c−3=9−3+5c | | 2x+8+5x=58+2x |

Equations solver categories